The petrogenesis of the Pliocene Araral stratovolcano in the Andean Central Volcanic Zone, Northern Chile - Mashego, Ramolokwane (Department of Geological Sciences, 2025)
The Altiplano-Puna Volcanic Complex (APVC) is a silicic volcanic complex in the Central Andean Volcanic Zone (CVZ). The APVC is underlain by the thickest known crust in a continental arc setting and the largest known magma body – the Altiplano-Puna Magma Body (APMB). Lavas of the APVC and CVZ are compositionally heterogeneous with elevated Sr isotope ratios relative to mantle-derived lavas and the rest of the Andean Volcanic Arc. The lavas are produced by subduction-induced magmatism and magma differentiation processes, such as crustal assimilation as the magma ascends through the thick crust. The APMB is a large regional melt anomaly proposed to be the source of APVC ignimbrites and the lavas of the APVC have a decreased degree of interaction with the APMB towards its margins. Mafic volcanism in the APVC is rare and is concentrated along the western margin of the APMB. These mafic lavas are predominantly Quaternary in age with some Pliocene lavas. Mafic volcanism in the APVC, and more specifically mafic volcanism during the Pliocene, is understudied.